Influence of homeopathy on the quality of eggs of quails stored - Wellington dos Santos; Rodrigo Garófallo Garcia; Bruna de Souza Eberhart; Jean Kaique Valentim; Felipe Cardoso Serpa; Maria Fernanda de Castro Burbarelli; Gisele Aparecida Felix; Mônica Filomena de Assis Souza (Acta Scientiarum. Animal Sciences, 2021)
This study aimed to evaluate the influence of homeopathic products in diets of quails in the egg quality when submitted to different storage periods. In the trial we used 200 Japanese quails in a completely randomized design with 4 diets: reference diet, vehicle used in homeopathic products and 2 homeopathic products - Fertsigo® and Ovosigo® with ten replicates of three eggs in each. Egg quality parameters were evaluated during 3 storage periods. Data were evaluated as repeated measures in time, the effects of the interactions between treatments and time as well as their isolated effects were verified. There was the interaction between homeopathic products and storage time in the parameters of albumen and yolk height, Haugh unit, and yolk index, in which a reduction was obtained over time. For egg weight, yolk, albumen and shell, percentage of albumen, and percentage of eggshell there was a significant effect only for homeopathy. The inclusion of homeopathic additives increased egg weight. It is indicated the addition of the product with homeopathic basis Ovosigo® and FertSigo® in diets of Japanese quails in the laying phase resulting in better egg and components but did not influence the quality maintenance of eggs of Japanese quails in the periods evaluated.